SCREENING OF LACTOBACTERIA AND BIFIDOBACTERIA STRAINS BY PROBIOTIC PROPERTIES - О. А. Полтавська; Н. К. Коваленко; I. Г. Успенський (Mìkrobìologìâ ì Bìotehnologìâ. Мікробіологія і біотехнологія, 2011)
As a result of screening carried out in accordance with modern requirements of WHO, strains of bifidobacteria B. animalis subsp. lactis 99, B. bifidum 102, Bifidobacterium sp. 271 and B.bifidum 278 have been selected as promising to create the probiotics for children, and strains of Lactobacillus sp. 25A, Bifidobacterium sp.82D and B. bifidum 34s – for creation of the probiotics for the middle-aged and elderly.